Influence of salts on selective coagulation of whey proteins and their application in the isolation of β-lactoglobulin - Jana HANUŠOVÁ; Miroslava MIHULOVÁ; Lenka DIBLÍKOVÁ; Ladislav ČURDA (Czech Journal of Food Sciences, 2014)
Whey proteins are an important constituent of milk, especially whey from cheese manufacture and have many valuable functional properties such as foaming and emulsifying ability or gel formation. Some whey proteins are sensitive to salt content in a solution. High or low salt content may lead to selective coagulation of these proteins. A part of whey proteins was precipitated by addition of 7% (wt) NaCl and β-lactoglobulin and caseinomacropeptide remained in the supernatant. It was necessary to demineralise the supernatant by electrodialysis for the selective coagulation of caseinomacropeptide from this material. Subsequently, ethanol was added and pH was adjusted. This reduction of the ionic strength and the addition of ethanol induced the selective precipitation of caseinomacropeptide (91.4% from the original amount of CMP). β-lactoglobulin of 91% purity remained in the solution.